From the constitution to the communicative construction of space - Steets, Silke; Knoblauch, Hubert (Communicative Constructions and the Refiguration of Spaces, 2022)
For centuries, the assumption that space preceded social reality was widespread in Western thought. Only in recent decades have voices been raised demanding that space be understood as socially produced. Based on a brief summary of the sociological debate on space, we propose to update Martina Löw’s Sociology of Space (2016, New York: Palgrave Macmillan; Raumsoziologie 2001, Frankfurt am Main: Suhrkamp) by connecting her relational approach to space with the theory of communicative constructivism (Knoblauch 2020, he Communicative Construction of Reality. London: Routledge). This allows us to anchor space in a triadic relationship unfolding between subjects and “objectivations” (Berger and Luckmann 1966, The Social Construction of Reality: A Treatise in the Sociology of Knowledge. New York: Penguin Books), resulting in processes of subjectivation and objectivation. It thus becomes clear that the (always fleeting) spatiality of the social is, first, realized in the embodied performance of communicative actions. However, in order to constitute a (more stable) space, spatiality must be consolidated and “hardened”, which can be described as a twofold process: Spatiality turns into space, on the one hand, through “material objectivations” and the way they mediate bodies with one another, and, on the other hand, through processes of subjectivation, by which we mean an (always perspectival) internalization of spatiality as knowledge. In applying our model to digital mediatization, new forms of space synthesis come into view that point to a refiguration of spac